Tourism Route Planning Route Based on Tourist Category using Orienteering Problem with Time Windows - Hapsari, Indri; Iswadi, Hazrul; Cahyadi, Yosvaldo Ongko (Prasetiya Mulya Publishing, 2019)
Indonesia has a large number of favorable tourism destinations, for example like Besuki in East Java that has some potential tourist attractions. The complexity to plan a tourism travel routes for particular tourist category become a problem. Hence, travel recommendations for tourists are required. To solve this problem, the first step is accumulating data from questionnaires, Google Map, TripAdvisor, and website of the Tourism Office in Besuki. The questionnaires were distributed to respondents with dominant age between 15-24 years (60%) and most of them were students (44%). Most respondents were single (74%) and traveling with their family (52%). Using LINGO, model Orienteering Problem with Time Windows (OPTW) with objective function is maximizing scores and having restrictions in opening and closing hours of each tourist attractions. The database that required are opening and closing hours, the distance between tourist attractions, and maximum tourist’s hours per day. Score for each tourist attraction and service time will be taken from each tourist category. There are 3 tourists’ categories such as Simplicity Searchers (42%), Cultural Purists (34%), and Reward Hunters (24%). Eventhough there is no significant difference among service time for all categories, the median service time will give different results in total score and routes.